PENGARUH KUALITAS PELAYANAN TERHADAP TINGKAT KEPUASAN PELANGGAN PERUSAHAAN INSTALASI TENAGA LISTRIK - Prabawa, Santosa Tri (ITB AAS Indonesia Surakarta, 2024)
This research aims to determine and analyze the influence of service quality on the level of customer satisfaction of electric power installation companies in Surakarta. The object of this research is PT. Serkolians Aman Nusantara Unit Surakarta. This research used 74 respondents as research samples and the sampling technique used a non-probability sampling method with purposive sampling technique. The data analysis method used is a quantitative analysis method which includes validity test, reliability test, classical assumption test, multiple linear regression analysis, hypothesis testing via t test, F test and R2 test. The F test results for all variables of physical evidence, reliability, responsiveness, assurance and empathy simultaneously influence the level of customer satisfaction with the calculated F test results > Ftable (4.73 > 2.34). Testing the t-test hypothesis shows that the physical evidence variable has a positive and significant effect on the level of customer satisfaction with a significant level of physical evidence of 0.17 < 0.05 and the tcount value (2.108) > ttable value (1.667). The reliability variable has a positive and insignificant effect with the results of a significant reliability value of 0.857 > 0.05, and the tcount value (0.181) < ttable value (1.667). The responsiveness variable has a positive and significant effect on the level of customer satisfaction with a significant responsiveness value of 0.049 < 0.05, and the calculated t value (2008) > ttable value (1.667). The guarantee variable has a positive and significant effect on the level of customer satisfaction with a significant guarantee value of 0.011 < 0.05, and the calculated t value (2.619) > ttable value (1.666) 0.11 < 0.05. The empathy variable has a positive and insignificant effect on the level of consumer satisfaction with a significant empathy value of 0.394 > 0.05, and a tcount value (0.858) < ttable value (1.667). The coefficient of determination test (R2) seen in the Adjusted R Square is 0.604, indicating that 60.4% of customer satisfaction at PT. Serkolians Aman Nusantara Surakarta Unit can be explained by the service quality variable.